2009
DOI: 10.1177/0748233709355731
|View full text |Cite
|
Sign up to set email alerts
|

Anticlastogenic effect of caffeic acid phenethyl ester on cisplatin-induced chromosome aberrations in rat bone marrow cells

Abstract: Caffeic acid phenethyl ester (CAPE) is an antioxidant that can scavenge free radicals and protect cellular macromolecules, including DNA and proteins, from oxidative damage induced by various agents. The protective effect of CAPE on cisplatin-induced chromosome aberrations has been determined in rat bone marrow cells. The animals were pretreated with a single dose of CAPE (10 micromol/kg body weight [b.w.]) injected intraperitoneally (i.p.) 24 hours before the administration of cisplatin and then sacrificed 24… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 29 publications
(40 reference statements)
0
4
0
Order By: Relevance
“…Previously, the synthesis technique of CAPE was reported by Yilmaz et al 15 Ready-made CAPE (Sigma-Aldrich, St Louis, MO, USA) was dissolved in absolute ethanol and further dilutions were made in saline. The systemic application dose of CAPE was chosen on the basis of the Grunberger et al 16 study.…”
Section: Methodsmentioning
confidence: 99%
“…Previously, the synthesis technique of CAPE was reported by Yilmaz et al 15 Ready-made CAPE (Sigma-Aldrich, St Louis, MO, USA) was dissolved in absolute ethanol and further dilutions were made in saline. The systemic application dose of CAPE was chosen on the basis of the Grunberger et al 16 study.…”
Section: Methodsmentioning
confidence: 99%
“…Ayla et al showed that, in sperm samples incubated with CAPE, the DNA damage was decreased with low chromatin condensation when compared to samples not incubated with CAPE, and at the same time, incubation with CAPE reduced the MDA levels [21]. Yilmaz et al investigated the anticlastogenic effect of CAPE on CP-induced chromosomal defects in rat bone marrow cells [22]. First, CAPE was applied (10 µmol/kg), and then 24 h following that, CP (5 mg/kg) was applied.…”
Section: Discussionmentioning
confidence: 99%
“…The only exception was the HT29 cell line, where CAPE given along with CPT-11 increased genotoxicity compared to the series with CPT-11 alone, but the differences was not significant statistically. Yilmaz et al [50] analyzed rat bone marrow cells to see the impact of CAPE on cisplatin-induced chromosomal aberrations. CAPE induced a statistically significant decrease in the number of abnormal metaphases and chromosomal aberrations compared to the absence of CAPE.…”
Section: Discussionmentioning
confidence: 99%
“…CPT-11 was added to the medium at 5, 10, 15, 30, 60, and 100 µM, whereas for SN38 it was 0.25, 0.5, 1, 5, 10, and 15 µM. For each concentration of CPT-11 and SN38, CAPE was added at the concentration equal to the IC 50 determined for each of the tested cell lines. The results obtained for experimental series CAPE + CPT-11 and CAPE+SN38 are shown in Figures 3 and 4, respectively.…”
Section: Antagonistic Effect Of Cape On Cpt-11 and Sn38mentioning
confidence: 99%